Synthesis, Molecular Structure from the X-ray Diffraction Data of the Powder (1E,1’E)-1,1’-(1,4-Phenylene)Bis(N-(Adamantan-1-yl)methanimine) - Hamed, Shukkur A. (Iraqi Journal of Science, 2021)
The title compound was synthesized by 2:1 condensation between adamantan-1-ylamine and benzene-1,4- dicarbaldehyde in n-BuOH and produced a good yield 87% of new bis Schiff base. The compound skeleton was affirmed by FTIR, 1H NMR, LC-MS, and X-ray powder diffraction. The structure was solved by a parallel tempering process and refined by using Rietveld refinement. Two adamantan-1-ylimino groups are connected in the anti-positions to the planar central 1,4-dimethylbenzene group. All rings of the adamantyl group possess normal chair conformation.